Peran Farmasi Klinis dalam Meningkatkan Keamanan Penggunaan Obat pada Pasien Geriatri : Tinjauan Literatur - Hapsari, Estuningtyas Ayu; Al Farisi, Taufiq; Aprilia Sinta, Riska (CV. Creative Tugu Pena, 2024)
With the aging population increasing worldwide, attention to the safety of drug use in geriatric patients is becoming increasingly important. Through a better understanding of the role of clinical pharmacy in this context, it is hoped that more effective strategies can be found to improve the quality of drug care for the geriatric population, thereby providing maximum benefits for patients' health and quality of life. Thus, the aim of this literature observation is to dig deeper into the role of clinical pharmacy in improving the safety of drug use in geriatric patients (Javier, 2023). The aim of exploring relevant literature, we can innovate approaches that have been proven effective, as well as identify challenges and opportunities in optimizing the role of clinical pharmacy in the care of geriatric patients (Annisa, 2012), adjusting doses based on physiological factors related to age, and providing education to patients and families about the correct use of drugs (Sari, 2015). Literature studies suggest that clinical pharmacy interventions, such as thorough medication review, drug counseling, and identification of potential drug interactions, can reduce the risk of side effects and increase patient compliance with drug therapy. Apart from that, health team collaboration between clinical pharmacists, doctors and nurses is also an important factor in ensuring the safe use of drugs in geriatric patients (Karnova, 2020). Keywords: Clinical Pharmacy, Safety of Drug Use, Geriatric Patients, Literature Review.